INVESTIGATION OF DRUG-RELATED PROBLEMS IN TYPE 2 DIABETES MELLITUS PATIENTS WITH MACROVASCULAR COMPLICATIONS: A CROSS-SECTIONAL STUDY - Alifia Putri Febrianty (Universitas Islam Negeri Alauddin Makassar, 2019)
Objective this study to identify and classify DRPs in type 2 diabetes mellitus patients with macrovascular complications. Method A cross-sectional observational study was conducted in type 2 diabetes mellitus outpatients with macrovascular complications at Makassar Regional Hospital, for two months (July and August 2018). The study complied with all clinical research requirements in accordance with the Declaration of Helsinki. Ethics committee approval was obtained from UIN Alauddin Makassar. Thirty eight prescriptions were collected for this study. Samples were recruited based on inclusion and exclusion criteria. The identification and classification of DRPs were according to the PCNE tool v 8.02. Result: The most common drug-related problems were adverse drug reactions (n = 73; 77.7%) of the therapeutic safety domain, followed by optimal therapeutic effects (n = 15; 15.9%) of the effectiveness domain and finally unneeded drugs therapy (n = 4; 4.3%) from other domains. The highest cause of DRPs was the required of drug information was not available (n = 73; 77.7%), followed by drugs not in accordance with the guidelines (n = 10; 10.6%). The results of identification and causes of DRPs obtained 101 causes of DRPs in T2DM patients with macrovascular complications. Interventions that have been made by pharmacists to doctors in the form of providing information, interventions given to patients in the form of giving drug counseling and providing interventions on drugs in the form of drug replacement and drug dosage and stopping drugs. The implementation of the intervention given by the pharmacist was well received but the implementation was not known to be the highest, at 58.8%. The status of the PTO intervention by the pharmacist was unknown because patients were outpatients at 58.8%. Conclusion: Pharmacists have identified and categorized DRPs that occur in T2DM patients with macrovascular complications in the form of potential problems that are adverse drug reactions (may) occur as well as problems that have occurred namely the effect of suboptimal drug therapy, unnecessary drug therapy and symptoms or indications that are not treated.